On metaphysics - Chisholm, Roderick M. (University of Minnesota Press, 1989)
On Metaphysics was first published in 1989. On Metaphysics brings together eighteen essays by a self-described analytic philosopher who is concerned with redirecting the linguistic emphasis in contemporary philosophy toward the traditional questions of metaphysics. The essays explore the most fundamental categories of reality: substance and attribute; parts and wholes; human freedom and the self; coming into being and passing away; and the nature of objective reference. Chisholm combines an ""internal"" approach to theory of knowledge with an ""intentional"" approach to metaphysics. The book t